The multifaceted role of the SASP in atherosclerosis: from mechanisms to therapeutic opportunities - Yu Sun; Xia Wang; Tianwei Liu; Xiaoyan Zhu; Xudong Pan (Cell & Bioscience, 2022)
Abstract Background The global population of older individuals is growing, and ageing is a key risk factor for atherosclerotic cardiovascular diseases. Abnormal accumulation of senescent cells can cause potentially deleterious effects on the organism with age. As a vital marker of cellular senescence, the senescence-associated secretory phenotype (SASP) is a novel mechanism to link cellular senescence with atherosclerosis. Main body In this review, we concretely describe the characteristics of the SASP and its regulation mechanisms. Importantly, we provide novel perspectives on how the SASP can promote atherosclerosis. The SASP from different types of senescent cells have vital roles in atherosclerosis progression. As a significant mediator of the harmful effects of senescent cells, it can play a pro-atherogenic role by producing inflammation and immune dysfunction. Furthermore, the SASP can deliver senescence signals to the surrounding vascular cells, gradually contributing to the development of atherosclerosis. Finally, we focus on a variety of novel therapeutic strategies aimed to reduce the burden of atherosclerosis in elderly individuals by targeting senescent cells and inhibiting the regulatory mechanisms of the SASP. Conclusion This review systematically summarizes the multiple roles of the SASP in atherosclerosis and can contribute to the exploration of new therapeutic opportunities.